ADVENTUROUS SAINT KABIR’S SOCIAL PHILOSOPHY: साहसिक संत कबीर का सामाजिक दर्शन - Kumar Bithore, Ashish (International Journal of Research -GRANTHAALAYAH, 2022)
There is a difference of opinion among many scholars regarding the birth of Kabir, that Kabir was given birth by a widow. At the same time, according to the belief of Kabir Panthis, at the time when nature had covered the sky with cloud. The birds were singing the welcome anthem with their tweets, at such a time a divine child appeared in the lotus flower blooming in the Lahtara pond. At the same time, some people say that Kabir was a Muslim by birth and at a young age he came to know about the alms of Hindu religion under the influence of Swami Ramanand. कबीर के जन्म् के विषय में अनेक विद्वानों का मतभेद है, कि कबीर को किसी विधवा ने जन्म दिया था। वहीं कबीर पंथियों की धारणा के अनुसार अतिरमणीय समय में जब प्रकृति ने नभमंडल को मेघमाला से अच्छादित कर रखा था। पक्षी अपने कलरव से स्वागत गान गा रहे थे ऐसे समय पर लहतारा तालाब में खिले हुए कमल-पुष्प में एक दिव्य बालक प्रकट हुआ हुआ। वहीं कुछ लोगों का कहना है कि कबीर जन्म् से मुसलमान थे और युवा अवस्था में स्वामी रामानन्द के प्रभाव से उन्हें हिन्दू धर्म की भिक्षा मालूम हुई।